Cytosolic malate and oxaloacetate activate S-type anion channels in Arabidopsis guard cells - Wang, Cun (New Phytol, 2018)
Intracellular malate–starch interconversion plays an important role in stomatal movements. We investigated whether malate or oxaloacetate from the cytosolic membrane side regulate anion channels in the plasma membrane of Arabidopsis thaliana guard cells. Physiological concentrations of cytosolic malate have been reported in the range of 0.4–3 mM in leaf cells. Guard cell patch clamp and two-electrode oocyte voltage-clamp experiments were pursued. We show that a concentration of 1 mM cytosolic malate greatly activates S-type anion channels in Arabidopsis thaliana guard cells. Interestingly, 1 mM cytosolic oxaloacetate also activates S-type anion channels. Malate activation was abrogated at 10 mM malate and in SLAC1 anion channel mutant alleles Interestingly, malate activation of S-type anion currents was disrupted at below resting cytosolic free calcium concentrations ([Ca(2+)](cyt)), suggesting a key role for basal [Ca(2+)](cyt) signaling. Cytosolic malate was not able to directly activate or enhance SLAC1-mediated anion currents in Xenopus oocytes, whereas in positive controls cytosolic NaHCO(3) enhanced SLAC1 activity, suggesting that malate may not directly modulate SLAC1. Cytosolic malate activation of S-type anion currents was impaired in ost1 and in cpk5/6/11/23 quadruple mutant guard cells. Together these findings show that these cytosolic organic anions function in guard cell ion channel regulation.